2022
DOI: 10.1097/md.0000000000031075
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of a novel prognostic model for thyroid cancer based on N7-methylguanosine modification-related lncRNAs

Abstract: Background: To construct and verify a novel prognostic model for thyroid cancer (THCA) based on N7-methylguanosine modification-related lncRNAs (m7G-lncRNAs) and their association with immune cell infiltration. Methods: In this study, we identified m7G-lncRNAs using co-expression analysis and performed differential expression analysis of m7G-lncRNAs between groups. We then constructed a THCA prognostic model, performed survival analysis and risk assessment for the THCA prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(57 reference statements)
1
0
0
Order By: Relevance
“…In this study, two OSRlncRNA of SAP30-DT (protective factors) and DPP4-DT (risk factors) were screened. Zhou et al [35] reported a prognostic model of THCA based on six N7-methylguanosine modi cationrelated lncRNAs, in which DPP4-DT was also a risk factor, which was consistent with the results of the present study. Zhang et al [36] constructed a risk prediction model for THCA prognosis and immune response based on ferroptosis-related lncRNAs (FRLs).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, two OSRlncRNA of SAP30-DT (protective factors) and DPP4-DT (risk factors) were screened. Zhou et al [35] reported a prognostic model of THCA based on six N7-methylguanosine modi cationrelated lncRNAs, in which DPP4-DT was also a risk factor, which was consistent with the results of the present study. Zhang et al [36] constructed a risk prediction model for THCA prognosis and immune response based on ferroptosis-related lncRNAs (FRLs).…”
Section: Discussionsupporting
confidence: 92%